Austria : Financial Sector Assessment Program Update Technical Note; Factual Update and Analysis of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2008)
This technical note highlights the financial sector assessment program update of Austria with factual update for effective banking supervision. Financial sector regulation and supervision should be conducted in the general public interest. Although authorities have acted effectively in recent cases of major problems, it is recommended that, within the legal framework in place, a set of practical provisions and procedures be elaborated for an orderly exit in case of failures and other stress situations.